An exploration of the degree of congruence, of the perspectives held by teachers and their adolescent students, regarding their roles and relationships - Brooks, Kathy (My University, 2012)
This study provides a narrative of the perspectives and beliefs of a group of teachers and adolescent students regarding their roles and relationships, with specific reference to the classroom. Data were collected through interviews and self inventories from four teachers and four students of a secondary school in Trinidad and Tobago. Among the findings were that: 1) both students and teachers felt that the curriculum was too extensive, resulting in duplication of effort; 2) one student wanted more collaboration among teachers with a view to recognizing and reducing the workload placed upon the students by teachers of the various subject areas; 3) one teacher expressed the view that the magnitude of the curriculum had negated the possibility of a pleasant classroom experience for the students; and 4) issues relating to class control, teacher-centredness, or student-centredness seemed to be related to the age of the students, who seemed to share the teachers' perspective on what their role was
Keywords: Teacher attitudes; Student attitudes; Student teacher relationship; Secondary school teachers; Secondary school students; Trinidad and Tobago; Classroom environment